1992
DOI: 10.2307/1131232
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Witnessed Affect on Information Processing in Children

Abstract: Children between the ages of 5 and 10 years watched a videotape of a child having a routine medical exam. Embedded within the scenes were systematic variations of depicted facial affect shown by doctor and child. Measures were taken of autonomic reactions and information-processing errors in response to positive, neutral, and negative affective cues. For 5-6-year-olds, processing errors were greatest in the negative affect condition. Additionally, peak increases in heart rate (HR) and skin conductance level (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 26 publications
1
26
1
Order By: Relevance
“…In contrast, insofar as young children rely on others to help them cope, young children who experience a novel stressor may become so aroused that they are not able to attend to the event. Lack of attention would lead to subsequently poorer memory, a pattern of results supported by other research (Bugental et al, 1992).…”
Section: Stress and Memorysupporting
confidence: 74%
See 4 more Smart Citations
“…In contrast, insofar as young children rely on others to help them cope, young children who experience a novel stressor may become so aroused that they are not able to attend to the event. Lack of attention would lead to subsequently poorer memory, a pattern of results supported by other research (Bugental et al, 1992).…”
Section: Stress and Memorysupporting
confidence: 74%
“…Children in the fire-alarm, or "stressed," group had significantly higher pulse rates than children in the radio, or "non-stressed," group and later provided fewer correct and more incorrect statements about their experience. Bugental et al (1992) found that 5-year-olds who exhibited increased heart rate while watching a video of a child receiving an inoculation made more mistakes when recalling the video than did 5-year-olds who did not exhibit an increase in heart rate. (No significant associations were found with older children, however).…”
Section: Stress Autonomic Arousal and Memorymentioning
confidence: 99%
See 3 more Smart Citations